A high-resolution time series of particulate matter fatty acids reveals temporal dynamics of the composition and quality available to zooplankton in a temperate coastal ocean. (August 2022) - McLaskey, Anna K.; Forster, Ian; Del Bel Belluz, Justin; Hunt, Brian P.V.
Highlights: Fatty acids primarily driven by seasonal phytoplankton production and community. Specific factors shifted seasonally, but FA nutrition remained high spring-fall. POM fatty acids correlated more with Chl a size classes than taxonomic observations. Variable FA:Chl showed notable heterotrophic components during summer and fall. Seasonal tradeoffs in size, abundance, and quality of prey for zooplankton. Abstract: Particulate organic matter (POM) forms the base of the pelagic food web, but is a complex category of material that undergoes substantial changes in quantity and quality across different time scales. As the primary consumers of POM, zooplankton are influenced by these fluctuations, resulting in shifts in the food web pathways that contribute to the production of higher trophic levels. We measured POM fatty acids, which are critical nutritional components in marine food webs, along with a suite of associated biotic and abiotic environmental conditions at a temperate coastal site over four years. Using these data, we investigated the co-occurring patterns of prey quality, quantity, and size, to develop a holistic understanding of how the prey field for zooplankton varies over the seasonal cycle and inter-annually. The seasonal pattern of POM fatty acids corresponded to the succession of phytoplankton taxa, but displayed stronger relationships to size-fractionated Chl a than taxonomic observations. Times with high micro-Chl biomass (spring and fall blooms) had the greatest concentrations of high quality food, but fatty acid levels remained high throughout the summer when Chl a concentrations dropped and the size distribution shifted towards pico-Chl. The 18-carbon polyunsaturated fatty acids 18:3ω3 (α-linolenic acid) and 18:4ω3 (stearidonic acid) increased during this time and were correlated with pico-Chl. In addition, the important nutritional factor for zooplankton and fish, the fatty acid ratio DHA:EPA (22:6ω3/20:5ω3), peaked during the middle of summer separately from the peak in Chl a . These seasonal patterns resulted in tradeoffs among the abundance, size, and nutritional quality of prey for zooplankton. We validated the basal sources of several fatty acids used as trophic markers within food web studies and in particular note their power for resolving size-based trophic connections. Interannual variability, e.g., the occurrence of fall diatom blooms and the timing of community shifts, is also discussed. This work lays the foundation for future studies of the zooplankton community at this location and the incorporation of realistic prey conditions into zooplankton studies.